2021
DOI: 10.1016/j.seizure.2021.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid findings in patients with seizure in the setting of COVID-19: A review of the literature

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 80 publications
(328 reference statements)
2
14
2
1
Order By: Relevance
“…This finding confirmed the hypothesis that SARS-CoV-2 can infiltrate the CNS, but the presence of SARS-CoV-2 was not associated with the severity of neuropathological changes, which occurred similarly in patients without SARS-CoV-2 brain infiltration [5]. On the other hand, the detection of SARS-CoV-2 in cerebrospinal fluid (CSF) of patients with seizures and COVID-19 disease is uncommon [6].…”
Section: Introductionsupporting
confidence: 70%
“…This finding confirmed the hypothesis that SARS-CoV-2 can infiltrate the CNS, but the presence of SARS-CoV-2 was not associated with the severity of neuropathological changes, which occurred similarly in patients without SARS-CoV-2 brain infiltration [5]. On the other hand, the detection of SARS-CoV-2 in cerebrospinal fluid (CSF) of patients with seizures and COVID-19 disease is uncommon [6].…”
Section: Introductionsupporting
confidence: 70%
“… 10 17 However, detection of SARS-CoV-2 in the CSF of patients with seizures who have COVID-19 is uncommon (13%), and even when it is present, the significance of this finding is unknown. 18 …”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of 69 patients with seizures in the setting of COVID-19 who underwent CSF testing showed that only 13% had positive CSF SARS-CoV-2 PCR [62]. Hence detection of SARS-CoV-2 in CSF of patients with seizures is uncommon, and seizures in patients with COVID-19 are unlikely to be due to direct viral invasion of the brain [62].…”
Section: Csf Findings In Patients With Covid-19 and Seizuresmentioning
confidence: 99%
“…A systematic review of 69 patients with seizures in the setting of COVID-19 who underwent CSF testing showed that only 13% had positive CSF SARS-CoV-2 PCR [62]. Hence detection of SARS-CoV-2 in CSF of patients with seizures is uncommon, and seizures in patients with COVID-19 are unlikely to be due to direct viral invasion of the brain [62]. This may lend additional support to the theory that seizures and epileptogenesis in patients with COVID-19 may occur because of neuroinflammatory reactions to the virus rather than direct CNS invasion.…”
Section: Csf Findings In Patients With Covid-19 and Seizuresmentioning
confidence: 99%